Answer:
g(x) = (x - a)² or
g(x) = (x + a)² or
g(x) = x² + a or
g(x) = (x + b)² + a or
g(x) = (x + b)² - a or
g(x) = (x - b)² + a or
g(x) = (x - b)² - a
Explanation:
Given equation:
f(x) = x²
This is the equation of a parabola with turning points at (0,0) facing up.
Now;
g(x) which is a shifted version of f(x) will have one of many forms depending on the nature of translation.
If f(x) = x² is shifted to the right by a units, then;
g(x) = (x - a)²
If f(x) = x² is shifted to the left by a units, then;
g(x) = (x + a)²
If f(x) = x² is shifted upwards by a units, then;
g(x) = x² + a
If f(x) = x² is shifted downwards by a units, then;
g(x) = x² - a
If f(x) = x² is shifted upwards by a units and to the left by b units, then;
g(x) = (x + b)² + a
If f(x) = x² is shifted downwards by a units and to the left by b units, then;
g(x) = (x + b)² - a
If f(x) = x² is shifted upwards by a units and to the right by b units, then;
g(x) = (x - b)² + a
If f(x) = x² is shifted downwards by a units and to the right by b units, then;
g(x) = (x - b)² - a